2006
DOI: 10.1007/s00276-006-0140-x
|View full text |Cite
|
Sign up to set email alerts
|

Finite element analysis of the strain distribution in the humeral head tubercles during abduction: comparison of young and osteoporotic bone

Abstract: Observing the simulation results led understanding of the pathology of certain fractures of the proximal end of the humerus. This study also helped explain why certain types of osteosynthesis fail due to tubercles reconstruction failures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 21 publications
1
18
0
3
Order By: Relevance
“…Biomechanical studies have demonstrated a greater com- MSS medial support screw pressive stress on the medial region than on the lateral during normal shoulder motion [20,21]. Continuous varus stress of the rotator cuff may result in varus displacement of the humeral head and collapse of the articular surface during early rehabilitation, when the fracture fails to achieve anatomical reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Biomechanical studies have demonstrated a greater com- MSS medial support screw pressive stress on the medial region than on the lateral during normal shoulder motion [20,21]. Continuous varus stress of the rotator cuff may result in varus displacement of the humeral head and collapse of the articular surface during early rehabilitation, when the fracture fails to achieve anatomical reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Фізико-механічні властивості біологічних тканин, що застосовувались у моделях, отримані з літературних джерел [4,5,7] (табл. 1).…”
Section: ìàòåð³àëè òà ìåòîäèunclassified
“…Es ampliamente aceptado considerar como isotrópicos el tejido cortical y esponjoso para caracterizar el comportamiento mecánico del hueso, aunque en realidad no lo son. Lo anterior permite simplificar el modelado del sistema, reduciendo considerablemente el tiempo de cómputo para la obtención de la respuesta a estudiar [29,39,41,42,43,44,45]. CLAVERT et al [44] identificaron el módulo de elasticidad obtenido a través de la experimentación con tejido cortical y esponjoso del extremo superior del húmero para hueso sano y con osteoporosis, ambos considerados como materiales isotrópicos.…”
Section: Mallado Y Propiedades De Los Materialesunclassified